Knowledge Creation and Emergence of Innovations - Tekic, Zeljko; Cosic, Ilija; Katalinic, Branko (International Journal of Industrial Engineering and Management, 2013)
This paper tackles the question: What determines the direction and intensity of the innovation activities from the perspective of knowledge? Research is based on a chronology of knowledge and innovation development in the remote communication in order to obtain a fuller and richer understanding of knowledge – innovation cycles. The results show that knowledge always tends to develop towards the idea of the ideal, while the direction of development of knowledge is determined by the difference between what is needed and what is currently possible. The intensity of converting knowledge into innovation is defined by the limitations arising from the condition of society (profitability, legality, ethics) and compliance with nature (sustainability). Article history: Received (25 October 2012); Revised (25 December 2012); Accepted (16 January 2013)